Understanding the effects of mild traumatic brain injury on the pupillary light reflex - Kenneth J Ciuffreda; Nabin R Joshi; James Q Truong (Concussion)
The pupillary light reflex represents an optimal visual system to investigate and exploit in the mild traumatic brain injury (mTBI) population. Static and dynamic aspects of the pupillary light reflex were investigated objectively and quantitatively in the mTBI population. Pupillary responsivity was found to be significantly delayed, slowed and reduced, but symmetrical in nature, and with a smaller baseline diameter, as compared with normals. Several pupillary parameters also discriminated between those with versus without photosensitivity. Thus, dynamic pupillometry provides several objective biomarkers for the presence of mTBI and photosensitivity, gives insight into the global sites of neurological dysfunction and possible related mechanisms, and should result in improved patient care.